Analisis Kompetensi Softskill Pada Staff Pengajar Perguruan Tinggi Swasta di Kota Medan - Dhian Rosalina; Kartika Yuliari (Universitas Kadiri, 2019)
Soft skills are interpersonal and intrapersonal skills that can boost individual performance, including the teaching profession. The purpose of this study was to determine the profile of soft skills held by lecturers as teaching staff in tertiary institutions. This research was conducted in Medan, North Sumatra. The research method used is research with a qualitative descriptive approach. The sampling technique used was purposive sampling with the number of respondents of one hundred and twenty people. The results of this study are the variables forming soft skills such as leadership, communication, effort, ethics have been perceived well by the respondents, and have become daily behavior, although there are a few behaviors that require improvement, such as discipline in the lecture time, while the soft forming variables are skills such as Organizational skills and group skills are perceived to be lacking in teaching and learning activities by the respondents. Soft skill adalah ketrampilan interpersonal dan intrapersonal yang dapat mengembangkan dan memaksimalkan kinerja termasuk profesi dosen. Tujuan dari penelitian ini adalah mengetahui profil softskill yang dimiliki oleh Dosen sebagai staff pengajar di perguruan tinggi. Penelitian ini dilaksanakan di Medan, Sumatera Utara. Metode penelitian yang digunakan adalah penelitian deskriptif kualitatif . Teknik sampling yang digunakan adalah purposive sampling dengan jumlah responden sebesar seratus duapuluh orang. Hasil dari penelitian ini adalah Variabel pembentuk soft skill seperti Leadership, komunikasi, effort, ethics sudah dipersepsikan baik oleh para responden, dan telah menjadi perilaku sehari hari, meskipun ada sedikit perilaku yang memerlukan perbaikan, seperti kedisiplinan terhadap waktu perkuliahan., sedangkan Variabel pembentuk soft skill seperti Organizational skill dan group skill dipersepsikan kurang dilakukan dalam kegiatan belajar mengajar oleh para responden.